Measurement Customer Satifaction Toward KEUKEN #5 - The City Hall Fairground Culinary Event Using Importance - Performance Analysis (IPA) - Juandha, Try; Indriani, Mia Tantri Diah (Journal of Business and Management, 2015)
Abstract â€“ The main theme of this research is Marketing and focus on measuring satisfaction level from Keuken #5 culinary event that organized by House The House based on Importance Performance Analysis (IPA). The IPA model which showed graphical representation of the data, whereby event organizations can see areas of strength and weakness from event attributes is divided into four quadrants, with importance on the y-axis and performance on the x-axis, according to Martilla and James the resources should be allocate to improve attributes that reside in quadrant I. The result of theÂ analysis showed the overall visitor satisfaction level for Keuken was scored 3.7 which reported between â€œOkâ€ and â€œSatisfiedâ€. Convenient parking, food/beverages prices, and shopping attributes item are attributes which reside in quadrant I and Â considered as main priority for improvement. Local food,Â come and go, clean site, attractive environment, event guide, and opening/closing time, are attributes lay in quadrant II which considered as attributes that should be maintained. Entertainment and good local restaurant attributes lay in quadrant IV which are considered as attributes that possibly overkill. Celebrity chef demos, festival souvenir, and cooking demonstration attributes lay in quadrant III which considered as last priority.Keywords: Keuken, culinary event, customer satisfaction, Importance-Performance AnalysisÂ